Large eddy simulation of the effect of hat fux on pollutant dispersion in an urban street canyon - Chan, Andy, Prof.; Cheung, Eric; Siddheshwar, Pradeep G., Dr. (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/